Biocompatibility of phosphorylcholine coated stents in normal porcine coronary arteries. Issue 3 (1st March 2000) - Whelan, D M; van der Giessen, W J; Krabbendam, S C; van Vliet, E A; Verdouw, P D; Serruys, P W; van Beusekom, H M M
Abstract : OBJECTIVE: To improve the biocompatibility of stents using a phosphorylcholine coated stent as a form of biomimicry. INTERVENTIONS: Implantation of phosphorylcholine coated (n = 20) and non-coated (n = 21) stents was performed in the coronary arteries of 25 pigs. The animals were killed after five days (n = 6), four weeks (n = 7), and 12 weeks (n = 8), and the vessels harvested for histology, scanning electron microscopy, and morphometry. MAIN OUTCOME MEASURES: Stent performance was assessed by studying early endothelialisation, neointima formation, and vessel wall reaction to the synthetic coating. RESULTS: Stent thrombosis did not occur in either group. Morphometry showed no significant differences between the two study groups at any time point. At five days both the coated and non-coated stents were equally well endothelialised (91% v 92%, respectively). At four and 12 weeks there was no difference in intimal thickness between the coated and non-coated stents. Up to 12 weeks postimplant the phosphorylcholine coating was still discernible in the stent strut voids, and did not appear to elicit an adverse inflammatory response. CONCLUSION: In this animal model the phosphorylcholine coating showed excellent blood and tissue compatibility, unlike a number of other polymers tested in a similar setting. Given that the coating was present up to 12 weeks postimplant with no adverse tissue reaction, it may be a potential candidate polymer for local drug delivery.